Competition, innovation, and the effect of knowledge accumulation - Alexander Steinmetz (University of Würzburg, Department of Economics, 2010)
The question this paper addresses is how the market structure evolves due to innovative activities when firms' level of technological competence is valuable for more than one project. The focus of the work is the analysis of the effect of learningbydoing and organizational forgetting in R&D on firms' incentives to innovate. A dynamic step-by-step innovation model with history dependency is developed. Firms can accumulate knowledge by investing in R&D. As a benchmark without knowledge accumulation it is shown that relaxing the usual assumption of imposed imitation yields additional strategic effects. Therefore, the leader's R&D effort increases with the gap as she is trying to avoid competition in the future. When firms gain experience by performing R&D the resulting effect of knowledge induces technological leaders to rest on their laurels which allows followers to catch up. Contrary to the benchmark case the leader's innovation effort declines with the lead. This causes an equilibrium where the incentives to innovate are highest when competition is most intense.
Keywords: L11; L13; O31; O41; 330; competition; innovation; knowledge; market structure; Industrielle Forschung; Investition; Wissen; Innovationswettbewerb; Marktstruktur; Theorie